FINANCING OF ELECTION CAMPAIGNS: TRANSPARENCY AND MONITORING - Bonini, Amanda; Figueiredo, Ana Clara Machado; França, Eduardo Alexandre; Lima , José Augusto; Leão , Keity Hellem Rodrigues; Silva, Lara Barbosa; Junior , Moises Feliciano Pereira; Souza, Thamirys Oliveira de; Valle, Luciano; Muniz, Aline de Assis Rodrigues Amaral; et al. (CIPEEX, 2025)
The financing of electoral campaigns is one of the most sensitive dimensions for maintaining democratic integrity. In Brazil, the prohibition of corporate financing, following the Supreme Federal Court’s decision in ADI 4.650/DF (2015), inaugurated a new phase based on public financing through the Special Campaign Financing Fund (FEFC). This study aims to comparatively analyze the impacts of public and private models on transparency, oversight, and electoral equity, considering their repercussions on the strengthening or weakening of democracy. Using a qualitative, exploratory, and bibliographic approach, reference works, official TSE data, and reports from the TCU and Transparency International were analyzed. The results indicate that public financing mitigated the direct influence of large economic groups but still presents distortions, such as the concentration of resources within party leadership and the underrepresentation of women’s and minority candidacies. Oversight of expenditures with public resources also proves deficient, with difficulties in traceability and the absence of effective sanctions. It is concluded that transparency and oversight do not depend exclusively on the model adopted but on the articulation between legal regulation, institutional control, and social participation. The study contributes to the debate on political reform and the need for mechanisms that ensure fairness in the electoral process.